2021
DOI: 10.1007/s42860-021-00115-y
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Exchange Modeling of Divalent Cation Adsorption on SWy-3 Montmorillonite

Abstract: Ion-exchange modeling is used widely to describe and predict ion-adsorption data on clay minerals. Although the model parameters are usually optimized by curve fitting experimental data, this approach does not confirm the identity of the adsorption sites. The purpose of the present study was to extend to divalent cations a previous study on the retention of monovalent cations on Na-saturated montmorillonite (NaMnt) which optimized some of the model parameters using density functional theory (DFT) simulations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
1
0
0
Order By: Relevance
“…The results obtained by ICP-MS when saturating NB with the NH 4 Cl solution showed there was an exchange mainly with monovalent cations, decreasing K +1 and Na +1 , which agrees with those previously reported by Lagaly [39], who determined that the cations susceptible to being replaced by divalent ions or NH 4 + is given in the series: Li +1 < Na +1 < H +1 < K +1 < NH 4 + < Mg +2 < Ca +2 . The presence and replacement of the divalent cations found in this study are similar to those reported by Li and Schulthess [40].…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained by ICP-MS when saturating NB with the NH 4 Cl solution showed there was an exchange mainly with monovalent cations, decreasing K +1 and Na +1 , which agrees with those previously reported by Lagaly [39], who determined that the cations susceptible to being replaced by divalent ions or NH 4 + is given in the series: Li +1 < Na +1 < H +1 < K +1 < NH 4 + < Mg +2 < Ca +2 . The presence and replacement of the divalent cations found in this study are similar to those reported by Li and Schulthess [40].…”
Section: Discussionsupporting
confidence: 91%